Preclinical characterization of SHR6390, a novel CDK 4/6 inhibitor, in vitro and in human tumor xenograft models. Issue 4 (26th February 2019) - Long, Fei; He, Ye; Fu, Haoyu; Li, Yun; Bao, Xubin; Wang, Quanren; Wang, Yigang; Xie, Chengying; Lou, Liguang
Abstract : Inhibition of the cyclin‐dependent kinase (CDK) 4/6‐retinoblastoma (RB) pathway is an effective therapeutic strategy against cancer. Here, we performed a preclinical investigation of the antitumor activity of SHR6390, a novel CDK4/6 inhibitor. SHR6390 exhibited potent antiproliferative activity against a wide range of human RB‐positive tumor cells in vitro, and exclusively induced G1 arrest as well as cellular senescence, with a concomitant reduction in the levels of Ser780‐phosphorylated RB protein. Compared with the well‐known CDK4/6 inhibitor palbociclib, orally administered SHR6390 led to equivalent or improved tumor efficacy against a panel of carcinoma xenografts, and produced marked tumor regression in some models, in association with sustained target inhibition in tumor tissues. Furthermore, SHR6390 overcame resistance to endocrine therapy and HER2‐targeting antibody in ER‐positive and HER2‐positive breast cancer, respectively. Moreover, SHR6390 combined with endocrine therapy exerted remarkable synergistic antitumor activity in ER‐positive breast cancer. Taken together, our findings indicate that SHR6390 is a novel CDK4/6 inhibitor with favorable pharmaceutical properties for use as an anticancer agent. Abstract : SHR6390, a novel orally available CDK 4/6 inhibitor, exhibits wide‐spectrum, potent antitumor activity against retinoblastoma‐positive cancers, with evidence of sustained target inhibition both in vitro and in vivo. SHR6390 was capable of overcoming acquired drug resistance to trastuzumab or tamoxifen, and combined with endocrine therapy exerted synergistic effects against breast cancer. Thus, these results provide a rationale for ongoing clinical trials of SHR6390.